A study of brachial artery flow mediated dilatation and carotid intima media thickness in subjects having risk factors for coronary artery disease - Sahai, Shweta; Sinha, Sumit (International Journal of Advances in Medicine, 2017)
Background: Endothelial dysfunction (ED) is an early phenomenon in atherosclerosis and often progresses to structural changes and clinical manifestations. Brachial artery flow mediated dilatation (BAFMD) has recently emerged as a reliable tool for assessment of ED. Carotid artery intima media thickness (CCAIMT) is an established tool for the detection of early structural atherosclerosis. This study was done to assess the reliability of BAFMD as a surrogate marker of atherosclerosis by comparing it to CCAIMT. Methods: Seventy-one subjects were divided in to Group I (n = 42, patients with overt cardiovascular disease; abnormal resting ECG or history of myocardial infarction/angina or an abnormal coronary angiogram), Group II (n = 17, apparently healthy individuals, with risk factors, but no overt cardiovascular disease) and Group III (n = 12, control, healthy individuals without risk factors). Ischemia induced BAFMD and CCAIMT were studied using ultrasound imaging along with presence of metabolic abnormalities. Results: Age ranged from 18-70 years with male predominance [42 (49.4%)]. Mean BAFMD in Group I, Group II and Group III was 6.68±3.52%, 7.39±3.62 and 11.65±4.32% respectively. Impaired BAFMD was highest in Group I [31 (73.80%)] compared to other two groups (p = 0.0002). Abnormal CCA-IMT was significantly higher in group I [33 (78.57%)] than in group II [9 (52.94%)] and Group III (3 (25%)] (p = 0.0018). Conclusions: Both BAFMD and CCAIMT can be used interchangeably as surrogate markers for endothelial dysfunction and atherosclerosis. BAFMD is a reliable tool for prediction of early atherosclerosis.